2006
DOI: 10.1074/jbc.m604826200
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of a Tight Cluster Surrounding Tyrosine 131 in the Native Conformation of Antithrombin III Activates It for Factor Xa Inhibition

Abstract: The native conformation of antithrombin III (ATIII) is a poor inhibitor of its coagulation pathway target enzymes because of the partial insertion of its reactive center loop (RCL) in its central A ␤-sheet. This study focused on tyrosine 131, which is located at the helix D-sheet A interface, adjacent to the ATIII pentasaccharide and heparin cofactor-binding sites and some 17 Å away from the RCL insertion. cluster at the helix D-strand 2A interface of native antithrombin contributes significantly to the stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A further 6‐fold rate enhancement, together with RCL expulsion, occurred when H5 bound, to give ∼3‐fold higher k 2 than wild‐type antithrombin bound to H5. Significantly, an earlier study in which only Y131 was changed to Ala or Leu found a similar effect, with greatly enhanced basal rate of factor Xa inhibition in the absence of heparin (25 to 29‐fold) and a further 8 to 12‐fold enhancement when H5 bound [9]. Since in both cases most of the activation occurred while the RCL hinge was still constrained by β‐sheet A, this raised doubts about the role of RCL hinge expulsion as the means of activation through engagement of a new favorable exosite.…”
Section: Problems With the Current Mechanismmentioning
confidence: 67%
“…A further 6‐fold rate enhancement, together with RCL expulsion, occurred when H5 bound, to give ∼3‐fold higher k 2 than wild‐type antithrombin bound to H5. Significantly, an earlier study in which only Y131 was changed to Ala or Leu found a similar effect, with greatly enhanced basal rate of factor Xa inhibition in the absence of heparin (25 to 29‐fold) and a further 8 to 12‐fold enhancement when H5 bound [9]. Since in both cases most of the activation occurred while the RCL hinge was still constrained by β‐sheet A, this raised doubts about the role of RCL hinge expulsion as the means of activation through engagement of a new favorable exosite.…”
Section: Problems With the Current Mechanismmentioning
confidence: 67%
“…Alternative conformation-specific orientations of side chains have been reported in other allosteric proteins, e.g. periplasmic (maltose) binding protein MalE [34], rhodopsin [35], integrin [36], DNA-binding receptor NtrC [37], and anti-thrombin III [38]. However, the consequences of the toggle switch-like effect on the conformation and function of allosteric proteins has not been studied thoroughly, nor are they fully appreciated.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Arg145 is placed within the heparin binding site of human AT [ 42 ]. Further, in native AT, Tyr131-Asn127-Leu130-Leu140-Ser142 forms a tight cluster at the helix D-strand 2A interface and tight interactions between Tyr131 and neighbouring hD, and s2A stabilizes the native conformation of AT; it has also been hypothesized and tested that disrupting this cluster would activate AT independently of heparin [ 43 ]. Helix D residues 120–124 make multiple van der Waals contacts with residues 161–166 of helix E, where the rotation of helix D on binding to heparin pivots on the side chain of Phe123 and clashes into helix E. Here, the movement of Tyr166 is considered one of the important events in the propagation of conformational change from the heparin binding site to the distant hinge region of the RCL, required for the allosteric activation of AT [ 44 ].…”
Section: Resultsmentioning
confidence: 99%